Differential Effects of Interruptions and Distractions on Working Memory Processes in an ERP Study - Zickerick, Bianca; Thönes, Sven; Kobald, S. Oliver; Wascher, Edmund; Schneider, Daniel; Küper, Kristina (Frontiers in Human Neuroscience, 2020)
Interruptions (interfering stimuli to respond to) and distractions (interfering stimuli to be ignored) have been shown to negatively impact performance, particularly in tasks requiring working memory (WM). This study investigated how these two types of external interference affect task performance and attentional and WM processes as indexed by specific event-related potentials (ERPs) of the EEG. A Continuous Number Task (CNT) was applied, in which participants had to either decide whether the current number (condition without WM load) or the sum of the current and the preceding number (condition with WM load) was odd or even while responding to interlaced single letters (interruptions) or ignoring them (distractions). Contrary to previous research, we did not find external interference to affect performance under WM load. Unexpectedly, our results rather show that performance was significantly improved in trials after distractions compared to before. This effect was reflected particularly in a significantly increased P3 mean amplitude indicating enhanced attentional reallocation to task-relevant stimuli. Interestingly, this P3 effect appeared independent of WM load and also following interruptions. This underpins the account of P3 amplitudes being modulated by the interval between two task-relevant stimuli rather than by overall task-difficulty. Moreover, a pronounced fronto-central and posterior slow wave following interference suggest more control resources to maintain task-relevant stimuli in WM independent of the preceding interfering stimulus. Our results thus suggest that the type and foreknowledge of external interference may modulate the amount of interference and may also facilitate resource preparation under WM load.